Hidrogenasi Minyak Nabati - Nasri Hardy Nasir (Balai Besar Kimia dan Kemasan, 1977)
Hydrogenation of edible oils is a liquid phase process in which gaseous hydrogen is dispersed and caused to dissolve in the heated oils, where, under the influence of a solid catalyst (ussually nickel), it combines with unsaturated fatty acid ra dicals. Hydrogenation increases the melting point and consistency of oils. In addition to its effect upon the melting point and consistency of oils and fats, hydrogenation improves the resistance of the edible oil products to atmospheric oxidation.